2010
DOI: 10.1007/s00125-009-1645-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue kallikrein levels in type 2 diabetes

Abstract: Aims/hypothesis We measured components of the kallikreinkinin system in human type 2 diabetes mellitus and the effects of statin therapy on the circulating kallikrein-kinin system. Methods Circulating levels of bradykinin and kallidin peptides, and high and low molecular weight kininogens, as well as plasma and tissue kallikrein, and kallistatin were measured in non-diabetic and diabetic patients before coronary artery bypass graft surgery. Tissue kallikrein levels in atrial tissue were examined by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
4
20
1
Order By: Relevance
“…Statin therapy improves endothelial function and possibly causes kinin generation at the endothelial surface, but the association between these drugs and the circulating kallikrein-kinin system has not been widely studied. A publication in type 2-diabetic patients found no differences in circulating bradykinin and other peptides and proteins of the kallikrein-kinin system following statin therapy [37] whereas our results suggest that statins may improve the patients' inflammatory status via the kallikrein-kinin system. Note that no patients of this study received angiotensinconverting enzyme inhibitors, which are well known to increase levels of bradykinin in blood by inhibiting its degradation [38] .…”
Section: Color Version Available Onlinecontrasting
confidence: 54%
“…Statin therapy improves endothelial function and possibly causes kinin generation at the endothelial surface, but the association between these drugs and the circulating kallikrein-kinin system has not been widely studied. A publication in type 2-diabetic patients found no differences in circulating bradykinin and other peptides and proteins of the kallikrein-kinin system following statin therapy [37] whereas our results suggest that statins may improve the patients' inflammatory status via the kallikrein-kinin system. Note that no patients of this study received angiotensinconverting enzyme inhibitors, which are well known to increase levels of bradykinin in blood by inhibiting its degradation [38] .…”
Section: Color Version Available Onlinecontrasting
confidence: 54%
“…Vascular calcification is a common complication of diabetic vasculopathy and atherosclerosis, and levels of elastases and kallikreins are elevated in diabetic patients as well as in atherosclerotic lesions 42, 43 . Our observations point toward new ways of explaining vascular calcification in these conditions and may lead to new strategies for limiting calcification.…”
Section: Discussionmentioning
confidence: 99%
“…This may also suggest that high levels of tissue kallikrein in diabetic patients might be a predisposing factor in the induction of type 2 diabetes due to the inhibition of glucose transfer to the tissues [22]. Plasma levels of tissue kallikreinhave been reported to be increased in type 2 diabetes as previously reported [23] In the present study however, we also observed high concentrations of plasma tissue kallikrein , which presumably be due to the hyperactivity of the BK-forming system to induce systemic metabolic abnormalities. It has been reported that tissue kallikrein activates B2R directly without BK generation [24].…”
Section: Commentarymentioning
confidence: 70%